Prevalencia de trypanosoma cruzi en reservorios domésticos en la parroquia Salatí cantón Portovelo durante el año 2013 - Fárez Noblecilla, Leonardo Arturo (2014)
In the Salatí Parroquia of the Canton Portovelo was investigated on prevalence (Trypanosoma cruzi) in domestic dogs reservoirs in this case, taking into account the percentage of infected animals according to race, gender, age and origin. The objectives were: 1. To establish the prevalence of Trypanosoma cruzi in the parish Salatí Canton Portovelo in 2013; 2. Determine infestation rates of Trypanosoma cruzi in dogs by age, sex, race and place of origin. The study area corresponds to a temperature of 18 to 22 degrees in the central area, the high areas of 5 to 15 degrees and 28 degrees downward 12-. The Salatí Parish is part of the watershed of the Rio Alta Puyango we find the Salatí Rio, Rio, Rio Ambocas Luis. Its altitude is 650 m s.n.m For this we proceeded to take samples from 158 dogs of the parish and of different characteristics related to sex, race, age and origin thereof. Once selected animals proceeded to extract blood with EDTA and then Elisa testing in the laboratories of the National Program for the Control of Chagas Disease SNEM. The results concluded with no prevalence of the disease in dogs Salatí Parish.